Nasogastric tube and outcomes of Clostridium difficile infection: A systematic review and meta‐analysis. Issue 1 (11th January 2018) - Wijarnpreecha, Karn; Sornprom, Suthanya; Thongprayoon, Charat; Phatharacharukul, Parkpoom; Cheungpasitporn, Wisit
Abstract: Aims: Clostridium difficile infection (CDI) is a major concern for public health worldwide. Interestingly, the risk of poor clinical outcomes of CDI in patients with nasogastric tube (NGT) insertion is still controversial. The aim of this study was to assess the outcomes of CDI in patients with NGT insertion. Methods: A literature search was performed using MEDLINE, EMBASE, and The Cochrane Database of Systematic Reviews from inception through November 2017. Studies that reported relative risks, odds ratios, or hazard ratios comparing the clinical outcome of CDI in patients with NGT versus those who did not were included. Pooled risk ratios (RR) and 95% confidence interval (CI) were calculated using a random‐effect, generic inverse variance method. Results: Eight observational studies were included in our analysis to assess the association between NGT insertion and risk of poor outcome of CDI. The pooled RR of severe or complicated clinical outcomes of CDI in patients with NGT insertion was 1.81 (95% CI: 1.17 to 2.81). Conclusions: This study demonstrated a statistically significant association between NGT insertion and risk of poor outcomes of CDI. This finding may impact clinical management and primary prevention of CDI. Avoidance of unnecessary NGT uses would improve the clinical outcomes of CDI.